Growing Kratky Basil in Trombe Wall Cavity: Energy Performance - Iryna Borys Bohoshevych; Hiroatsu Fukuda (Applied Sciences)
This year-long experimental study, conducted in Kitakyushu, Japan, evaluates the performance of a retrofitted Trombe wall designed to cultivate hydroponically grown basil plants, aiming to enhance its year-round usability. The results show that the addition of plants reduced overheating and moderated temperature fluctuations, but also led to a 30.2% decrease in absorption and a 49.4% decrease in dissipation efficiency compared to a traditional Trombe wall. Seasonal variations influenced the suitability of the space for cultivation, with optimal conditions occurring in spring and summer, while autumn and winter posed challenges due to extreme temperature fluctuations. The daily energy balance was largely unaffected by factors such as leaf transpiration, spontaneous evaporation, additional ventilation, or increased appliance use, as these were overshadowed by the primary thermal processes: solar gains and conductive losses. Although the modified TW still provided passive heating, its energy output was reduced to approximately 10,000 MJ annually, compared to the baseline 14,000 MJ. The study suggests that alternative designs, including increased thermal mass, improved ventilation and better plant selection and could improve both cultivation and energy efficiency. Ultimately, while the green TW is best suited for seasonal use, it offers ecological and social benefits, such as local food production and CO2 fixation, highlighting its potential for integration into sustainable architectural practices.